Bioinformatic Analysis of Crosstalk Between circRNA, miRNA, and Target Gene Network in NAFLD - Du, Cen; Shen, Lan; Ma, Zhuoqi; Du, Jian; Jin, Shi (Frontiers in Genetics, 2021)
Background: The majority of chronic liver disease is caused by nonalcoholic fatty liver disease (NAFLD), which is one of the highly prevalent diseases worldwide. The current studies have found that non-coding RNA (ncRNA) plays an important role in the NAFLD, but few studies on circRNA. In this study, genes, microRNA (miRNA), and circular RNA (circRNA) associated with NAFLD were found by bioinformatic methods, bringing a novel perspective for the prevention and treatment of NAFLD. Methods: Expression data of GSE63067 was acquired from Gene Expression Omnibus (GEO) database. The liver samples were collected from the people diagosed with NAFLD or not. Differentially expressed genes (DEGs) were obtained from the steatosis vs. the control group and nonalcoholic steatohepatitis (NASH) vs. the control group using the GEO2R online tool. The overlapping genes remained for further functional enrichment analysis and protein-protein interaction network analysis. MiRNAs and circRNAs targeting these overlapping DEGs were predicted from the databases. Finally, the GSE134146 dataset was used to verify the expression of circRNA. Result: In summary, 228 upregulated and 63 downregulated differential genes were selected. The top 10 biological processes and relative signaling pathways of the upregulated differential genes were obtained. Also, ten hug genes were performed in the Protein-protein interaction (PPI) network. One hundred thirty-nine miRNAs and 902 circRNAs were forecast for the differential genes by the database. Ultimately, the crosstalk between hsa_circ_0000313, miR-6512-3p, and PEG10 was constructed. Conclusion: Hsa_circ_0000313-hsa-miR-6512-3p-PEG10 and its related non-coding RNAs may take part in NAFLD's pathogenesis, which could be the potential biomarkers of NAFLD in the future.